Tunnelling Behavior: Exploring Corporate Governance and Ownership Structure - Cahya Mahardika Putra Perdana; Adib Minanurohman (Jurnal Akuntansi dan Keuangan, 2024)
This paper investigates the impact of corporate governance quality and ownership structure on tunnelling behaviour in Indonesia, specifically examining the moderating effect of the number of subsidiaries. The study utilized quantitative research methods and secondary data from the Indonesia Stock Exchange, company websites, and relevant journals. The sample consisted of 474 observations from listed companies on the IDX, excluding non-financial firms, covering the period from 2016 to 2019. Statistical analyses, including Pearson Correlation, OLS Regression, and Moderated Regression, were conducted using STATA 14.2 software. The results indicate that managerial ownership, government ownership, and corporate governance quality positively influence tunnelling behaviour, while domestic ownership has a negative impact. Foreign ownership, on the other hand, does not significantly affect tunnelling behaviour. Notably, the number of subsidiaries strengthens the relationship between corporate governance quality and tunnelling behaviour.